Stress among employees in psychiatric nursing - Nemec, Urška (Obzornik zdravstvene nege, 2017)
Introduction: Evidence suggests that stressful situations are frequent in the field of psychiatry and that professionals working in this speciality are more prone to stress. Stressful situations may be compounded by ignoring the principles and strategies of therapeutic communication in all interactions with patients. The purpose of the research was to determine the presence of stress among the nursing team members. Methods: The research is based on a quantitative methodology; the data were collected using a semi-structured questionnaire. The sample consisted of 73 nurses working in a special social welfare institution (n = 37) and in a psychiatric hospital (n = 36). The survey was conducted in the first half of the year 2016. Descriptive statistics and chi-square test were used. Results: The list of stress factors most frequently reported by the participants include low pay (n = 40, 55 %), poor interpersonal relationships in the workplace (n = 23, 32 %), and the sense of insecurity due to unpredictable behaviour of patients (n = 32, 44 %). One fifth of the respondents are regularly subjected to patient physical violence and psychological abuse in the workplace (n = 14, 19 %) and a large majority (n = 53, 72.5 %) are frequently exposed to dangerous situations. The respondents are not fully aware of the crucial importance of therapeutic communication with the patients (n = 38, 52 %). Discussion and conclusion: It is impossible to completely avoid stressful situations in psychiatric settings. Psychiatric nurses should possess good communication skills and the ability to develop good interpersonal relationships.
Keywords: burnout; dejavniki stresa; delovna mesta; izgorelost; nasilje pacientov; patient violence; stress factors; terapevtska komunikacija; therapeutic communication; workplace